Classificação dos fatores de risco relacionados com a produtividade da construção civil - Chaves, Lárdner Gadelha; Campos, Vanessa Ribeiro (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The activities that seek to improve productivity are considered one of the main concerns of construction companies. Studies on this topic provide a better understanding as well as initiatives to make processes more efficient. In this context, this paper identifies the risk factors that most affect productivity in the construction industry, and proposes a classification for them in order to identify its main sources of occurrence. A bibliographical study from periodicals and scientific events was carried out with a total of 17 papers that identified and hierarchized these factors. Thus, the risks were classified according to four categories, presented according to their order of importance: process, materials, environment and workers. Finally, some measures are indicated to mitigate or prevent the occurrence of these phenomena.